Perspectives, Treatment Goals, and Approaches of Prevention-Specialist Mental Health Professionals in Working with Clients Attracted to Children - Flynn, Susan (My University, 2024)
The provision of effective mental health services to individuals attracted to children is rapidly expanding. However, these services have not yet been integrated into general mental healthcare systems and are mainly offered by organizations that predominantly provide services to child sexual abuse perpetrators. Little is known about the perspective, treatment goals, and approaches employed by prevention-specialist mental health professionals when working with clients attracted to children. To address this gap, we used purposive sampling to recruit 10 practitioners who had experience of working in prevention settings with clients attracted to children. After conducting semi-structured interviews and analyzing data through interpretative phenomenological analysis, we identified three main themes and four subthemes within the data. While most participants believed that attraction to minors is unmodifiable or doubted the possibility of modifiability, this belief did not necessarily manifest in their practice. Participants stressed the importance of finding safe alternatives for clients and highlighted the significance of accessing evidence-based information on alternative sexual outlets, such as sex dolls. One overarching theme that emerged across all themes and within participants' accounts was the concern of escalation, indicating a fear that pedophilic fantasies or alternative sexual outlets such as sex dolls could potentially lead to sexual offenses. The findings shed light on the approach of prevention-specialist mental health professionals in working with clients attracted to children and may be used to inform future intervention plans to facilitate service provision to this population.
PUBLISHED
https://doi.org/10.1177/10790632241268465
Keywords: Prevention-specialist mental health professionals, Treatment goals and approaches, Pedophilia, Minor attraction